A simple method of injecting tumescent fluid for liposuction - Arindam Sarkar; Sasanka Sekhar Chatterjee (Indian Journal of Plastic Surgery)
Injection of tumescent fluid is essential to obtain a painless and relatively bloodless liposuction. There are many methods of injecting the tumescent fluid like power pumps, syringes and pressure cuffs. Our method consists of applying air pressure within the plastic transfusion fluid bottle by pricking with a wide bore needle and connecting it to a sphygmomanometer balloon pump. By inflation of the balloon pump and thus increasing pressure inside the plastic bottle, the rate and volume of infusion can be controlled. By applying the cuff outside the bottle the visibility inside is impaired and the bottle gets collapsed preventing a continued pressure and thereby impairing both the quantity as well as the rate of infusion. Power pumps are expensive. This method is inexpensive, infused volume of fluid being visible and the rate of infusion controllable.